Modified solid electrolyte powder, preparation method thereof and application of modified solid electrolyte powder in lithium ion battery
By using a dual-function coating formed by assembling a silane coupling agent and a hydrophobic ionic liquid on the surface of LLZO, the problems of moisture and residual alkali on the surface of LLZO are solved, and the electrochemical performance and safety of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202411598866.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
There is a large amount of moisture and residual alkali on the surface of LLZO solid electrolyte, which leads to a decrease in its ionic conductivity and affects the cycle life and safety of lithium-ion batteries.
The dual-function coating layer formed by assembling silane coupling agent and hydrophobic ionic liquid is used to modify the surface of oxide electrolyte powders such as LLZO to remove moisture and residual alkali, and improve the stability of the material and the ease of blending.
It effectively improves the ionic conductivity of the positive electrode material and the electrochemical performance of the blended battery, enhances the cycle stability and safety of the battery, and simplifies the process and reduces production costs.
Smart Images

Figure BDA0005129017640000121 
Figure BDA0005129017640000131 
Figure HDA0005129017710000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a modified solid electrolyte powder, a preparation method thereof and an application thereof in lithium ion batteries. Background Art
[0002] The rapid development of the electric vehicle industry has put forward higher demands on power batteries. The battery life, cycle life and safety have become issues of common concern in the industry. As an important component of power batteries, positive electrode materials have a significant impact on battery performance. Among them, ternary positive electrode materials LiNi x Co y Mn z O2 has attracted widespread attention due to its high energy density, but safety and cycle life remain the main problems in its development process.
[0003] In recent years, oxide solid electrolytes have developed rapidly and have been applied to diaphragm coating, cathode material coating and blending, electrolyte blending, etc., aiming to improve the cycle life, energy density, safety and other performance of battery cells. Among them, cubic Garnet-type lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , hereinafter referred to as LLZO) has a high – -4 The ionic conductivity of S / cm can reach ~10 after doping – 3 S / cm, has received the most extensive attention and research. x Co y Mn z The addition of O2 can absorb the heat generated by the positive electrode active material and the gas generated by the oxidation and decomposition of the electrolyte, effectively improving the thermal stability and safety and maintaining the battery cell cycle capacity. Secondly, LLZO has high ionic conductivity, low cost, and is easy to mass produce.
[0004] However, during the sanding process, conventional LLZO generates a large number of hydroxyl groups on the surface, which will increase its water absorption capacity. Excessive moisture will reduce ionic conductivity, amplify powder microcracks, and change internal structure and strain. Moreover, LLZO will react with water to form Li + / H +The exchange of LiOH will increase the alkalinity of the positive electrode material. In the process of mixing the positive electrode slurry, gel-like substances will be generated, which will reduce the bonding strength between the slurry and the electrode. It is easy to have side reactions with the electrolyte during the charge and discharge process. Furthermore, LiOH will react with the CO2 gas in the battery to form a Li2CO3 contamination layer, which will significantly increase the interface impedance and reduce the ionic conductivity, thus affecting the battery performance. Therefore, it is necessary to take appropriate methods to eliminate the residual alkali on the surface of LLZO and other materials.
[0005] Among them, the method of treating the surface of LLZO materials to reduce the content of LiOH and Li2CO3 pollutants mainly uses conventional surface coating methods, but the high-temperature treatment stage often causes lithium loss on the LLZO surface and generates impurities that hinder lithium ion transmission. This makes the application of LLZO and other materials in positive electrode blending ineffective, which to a certain extent limits the promotion and application of LLZO materials. Summary of the invention
[0006] In view of the defects of the existing treatment methods for reducing the surface moisture of LLZO solid electrolyte and removing residual alkali, the present invention provides a modified solid electrolyte powder, a preparation method thereof and application in lithium ion batteries. The application of the modified solid electrolyte powder provided by the present invention can further improve the ionic conductivity of the positive electrode material and the electrochemical performance of the blended battery cell.
[0007] The invention provides a modified solid electrolyte powder, which comprises an oxide solid electrolyte substrate and a coating layer formed on the surface of the substrate, wherein the coating layer is formed by assembling a silane coupling agent and a hydrophobic ionic liquid.
[0008] In some embodiments, the oxide solid electrolyte substrate is composed of LISICON-type, garnet-type, perovskite-type or NASICON-type oxide electrolyte.
[0009] In some embodiments, the coating layer has a thickness of less than 10 nm; the modified solid electrolyte powder is hydrophobic, and the initial residual alkali content is less than 0.2 wt %.
[0010] The present invention provides a method for preparing a modified solid electrolyte powder, comprising the following steps:
[0011] Providing a hydrolyzate of a silane coupling agent;
[0012] The oxide solid electrolyte powder and the hydrolyzate of the silane coupling agent are mixed and reacted to obtain an intermediate powder;
[0013] The hydrophobic ionic liquid is mixed with the intermediate powder and reacted to obtain a modified solid electrolyte powder with a coating layer on the surface.
[0014] In some embodiments, the silane coupling agent is a fluorinated alkyltrialkoxysilane and / or a trimethoxyalkylsilane, further selected from the group consisting of nonafluorohexyltrimethoxysilane, heptadecafluorooctyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, trimethoxyoctadecylsilane, trimethoxyhexadecylsilane, trimethoxydodecylsilane, trimethoxy-n-propylsilane and trimethoxymethylsilane.
[0015] In some embodiments, the preparation of the hydrolyzate of the silane coupling agent includes: allowing the silane coupling agent to undergo a hydrolysis reaction in a mixed solution of ethanol and water, wherein the mass ratio of ethanol to water in the mixed solution is (5-10):1, the temperature of the hydrolysis reaction is 50-90°C, the time is 1-2h, and the pH value is adjusted to 2-4 to obtain a hydrolyzed solution of the silane coupling agent.
[0016] In some embodiments, the oxide solid electrolyte powder is LLZO powder, and is mixed with the hydrolyzate of the silane coupling agent in the form of an ethanol dispersion, and the mass ratio of the oxide solid electrolyte powder to ethanol is (10-30): (70-90); an intermediate powder ethanol dispersion is obtained by sand grinding.
[0017] In some embodiments, the hydrophobic ionic liquid is a methylimidazole fluorine-containing ionic liquid, further comprising one or more of 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazole tetrafluoroborate, 1-ethyl-3-methylimidazole hexafluorophosphate and 1-butyl-3-methylimidazole hexafluorophosphate.
[0018] In some embodiments, after the hydrophobic ionic liquid is mixed with the intermediate powder, the mixture is stirred for reaction for 0.5-5 hours, and then dried to obtain a modified solid electrolyte powder having a coating layer on the surface.
[0019] The present invention provides a positive electrode sheet, comprising a positive electrode active material, and further comprising: the modified solid electrolyte powder as described above or the modified solid electrolyte powder obtained by the preparation method as described above;
[0020] The positive electrode active material is one or more of lithium cobalt oxide, lithium iron phosphate and ternary positive electrode materials; the mass ratio of the positive electrode active material to the modified solid electrolyte powder is (97-98): (0.1-1).
[0021] The invention provides a lithium ion battery, which comprises the positive electrode sheet.
[0022] Compared with the prior art, the present invention proposes a technology for coating and modifying the surface of oxide electrolyte powders such as LLZO using a two-component functional layer of a silane coupling agent (SCA) and a hydrophobic ionic liquid (IL), wherein a modified solid electrolyte powder can be recorded as LLZO@SCA-IL (which can be replaced by other oxide solid electrolyte substrates). In the present invention, the functional groups of the silane coupling agent after hydrolysis can react with the hydroxyl groups on the surface of the oxide electrolyte to form a cross-linked structure, thereby effectively isolating the pollution of water and carbon dioxide in the air, improving the stability of materials such as LLZO, facilitating storage in the air, and enhancing the ease of mixing LLZO and the like in the positive electrode material. In addition, in the coating layer containing a silane coupling agent, the present invention uses a hydrophobic ionic liquid to exchange ions with the non-hydrolyzable group halogen of the silane coupling agent to form a self-assembled monolayer. In addition to ensuring the hydrophobic function of LLZO, the two-component functional coating layer further reduces the interface contact impedance between the oxide electrolyte and the positive electrode material, thereby improving the ionic conductivity of the positive electrode material and the electrochemical performance of the mixed battery cell.
[0023] On the other hand, in the preparation method of the present invention, silane coupling agent and hydrophobic ionic liquid are used to carry out surface coating modification on materials such as LLZO. The whole process does not require additional equipment and complicated processes, and can be operated on the basis of existing equipment. No toxic or harmful substances are generated during the coating process, and it is easy to produce in large quantities. Moreover, no impurities are generated after coating, and there is no other adverse effect on the LLZO material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of the reaction principle for preparing modified solid electrolyte powders in some embodiments of the present invention;
[0025] Figure 2 is the infrared spectrum of the modified LLZO powder of Example 1;
[0026] Figure 3 is a transmission electron microscope image of the modified LLZO powder of Example 1;
[0027] Figure 4 : The water contact angle of the LLZO powder of Example 1 before and after modification. DETAILED DESCRIPTION
[0028] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the drawings and the like in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The invention provides a modified solid electrolyte powder, which comprises an oxide solid electrolyte substrate and a coating layer formed on the surface of the substrate, wherein the coating layer is formed by assembling a silane coupling agent and a hydrophobic ionic liquid.
[0030] The present invention accordingly provides a method for preparing a modified solid electrolyte powder, comprising the following steps:
[0031] Providing a hydrolyzate of a silane coupling agent;
[0032] The oxide solid electrolyte powder and the hydrolyzate of the silane coupling agent are mixed and reacted to obtain an intermediate powder;
[0033] The hydrophobic ionic liquid is mixed with the intermediate powder and reacted to obtain a modified solid electrolyte powder with a coating layer on the surface.
[0034] The modified solid electrolyte powder of the present invention can further improve the ionic conductivity of the positive electrode material and the electrochemical performance of the mixed battery cell. In addition, the modification method of the present invention is simple and easy to implement, and is suitable for mass production.
[0035] In order to achieve the above purpose, the technical solution of the embodiment of the present invention is as follows:
[0036] The oxide solid electrolyte substrate described in the embodiment of the present invention has a coating layer on its surface, and the raw materials of the coating layer include a silane coupling agent and a hydrophobic ionic liquid.
[0037] The oxide solid electrolyte substrate is composed of LISICON, garnet, perovskite or NASICON oxide electrolyte, preferably garnet or NASICON oxide electrolyte; the method of the embodiment of the present invention has certain universality for the modification of oxide electrolyte powder. In some embodiments, the oxide solid electrolyte substrate is composed of LLZO, which has high ionic conductivity.
[0038] Preferably, the present invention is specifically illustrated with LLZO as the substrate; the particle size of the LLZO powder involved can be 500-600nm, preferably 550-570nm. That is, the modified solid electrolyte powder provided in the embodiment of the present invention is a LLZO powder coated and modified with a silane coupling agent and a hydrophobic ionic liquid, which can effectively remove moisture from the surface of LLZO, reduce the content of impurities such as residual alkali and lithium carbonate, and facilitate storage. At the same time, it can improve the stability in the blending of ternary positive electrode materials, etc., and enhance the electrochemical performance and safety of the battery cell.
[0039] The embodiment of the present invention can prepare LLZO powders with dual-component functional coatings of silane coupling agent and hydrophobic ionic liquid. The specific reaction principle involved can be found in Figure 1 .
[0040] Silane coupling agent is a type of silane that contains two different chemical groups (organic functional groups and hydrolyzable groups) in one molecule. Its general molecular formula is (YR) n SiX (4-n) (n=1,2), where YR is a non-hydrolyzable organic functional group, Y represents an alkenyl group and a hydrocarbon group with a terminal functional group Y (Cl, NH2, SH, N3, OCOMe, CH=CH2, NCO, etc.), and X mainly includes hydrolyzable organic functional groups such as methoxy (OCH3), ethoxy and other alkoxy groups, which can undergo hydrolysis reaction and generate Si-OH groups. In some embodiments of the present invention, the group X3 in the silane coupling agent is (OCH3)3, which can undergo condensation, dehydration and other chemical reactions with the hydroxyl groups on the surface of the powder such as LLZO after hydrolysis, that is, the silane coupling agent will form a Si-O covalent bond with the powder surface, so that the silane coupling agent is evenly and firmly coated on the surface of the oxide electrolyte powder.
[0041] In an embodiment of the present invention, one end of the silane coupling agent molecule has a hydrolyzable alkoxy group, and the other end is preferably a non-polar alkane group substituted by a halogen atom (such as fluorine F), which has a certain hydrophobic effect; it is preferably a fluorinated alkyl trialkoxysilane and / or a trimethoxyalkyl silane, more preferably nonafluorohexyl trimethoxysilane, heptafluorooctyl trimethoxysilane, heptafluorodecyl trimethoxysilane, heptafluorodecyl triethoxysilane, trimethoxyoctadecyl silane, trimethoxyhexadecyl silane, trimethoxydodecyl silane, trimethoxy n-propyl silane and trimethoxymethyl silane. In addition, the embodiment of the present invention preferably contains a silane coupling agent with a long carbon chain, such as an alkyl chain with 6 to 20 carbon atoms, which helps to enhance the hydrophobic effect.
[0042] The hydrolysis of the silane coupling agent described in some embodiments of the present invention specifically includes:
[0043] (1) Take a certain mass ratio of anhydrous ethanol and pure water (deionized water is generally used in the laboratory, and the mass ratio of the two can be 8:1), dissolve them in a glass beaker to form a mixed solution, and place the mixed solution on a magnetic stirrer to stir evenly, and the stirring speed can be 1000-3000 r / min;
[0044] (2) The pH can be adjusted by adding glacial acetic acid solution to the stirred mixed solution to adjust the pH value to 2-4;
[0045] (3) then adding the silane coupling agent (the mass ratio of the silane coupling agent to the mixed solution may be 1:40) into the mixed solution with a pH value of 2-4, and stirring and mixing uniformly;
[0046] (4) Raising the temperature to 50-90° C., preferably 60-80° C., to allow the silane coupling agent to undergo a sufficient hydrolysis reaction in a mixed solution of ethanol and pure water for 1-2 hours to obtain a hydrolyzed solution of the silane coupling agent.
[0047] The preferred embodiment of the present invention performs surface modification on LLZO powder, and the specific steps are as follows:
[0048] S1. Mix LLZO powder and anhydrous ethanol in a mass ratio of (10-30): (90-70) to form a mixed solution; that is, the mass ratio of the oxide solid electrolyte powder to ethanol is preferably (10-30): (70-90), which is conducive to forming a uniform solution;
[0049] S2. The mixed solution can be placed on a high-speed stirrer or in a high-speed mixer and dispersed for 0.5-1h at a stirring speed of 1000-2000r / min to form a uniform dispersion;
[0050] S3, adding the hydrolyzed silane coupling agent solution (i.e., the hydrolyzed solution of the silane coupling agent) into the dispersion before the sand milling begins, wherein the mass ratio of the dispersion to the hydrolyzed solution is preferably (30-60): (10-5);
[0051] S4, start sand grinding, the diameter of the sand grinding zirconium ball can be 0.3mm, the speed of the sand mill is preferably 2000r / min, and the preliminary modified LLZO ethanol dispersion is obtained after sand grinding;
[0052] S5, adding the hydrophobic ionic liquid to the preliminarily modified LLZO ethanol dispersion, preferably using a magnetic stirrer to heat and stir for 0.5-5h to further modify the preliminarily modified LLZO; wherein the heating temperature range may be 40-80°C, the stirring time range is preferably 1-4h, and the rotation speed may be 1000-1500r / min;
[0053] S6. The dispersion further modified by the ionic liquid can be dried in a blast oven, the drying temperature is preferably 150-200°C, the time is 4-10h, preferably 5-8h, to obtain a dry modified LLZO powder, and finally it can be fully ground manually in an agate mortar to form the final modified solid electrolyte powder.
[0054] Ionic liquids (ILs) are composed of anions and cations at room temperature, and have stable chemical properties, low flammability, high ionic conductivity, and some are hydrophobic. The embodiments of the present invention use hydrophobic ionic liquids, which have ionic conductivity and certain hydrophobicity, and have high solubility in organic solvents; based on the principle of ion exchange, the anion groups of the hydrophobic ionic liquids are exchanged with the non-hydrolyzable end halogens of the silane coupling agent, thereby forming a two-component functional coating layer of the silane coupling agent and the ionic liquid.
[0055] The hydrophobic ionic liquid described in the present invention is preferably a methylimidazole fluorine-containing ionic liquid, more preferably one or more of 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ([EMIM][TFSI]), 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ([BMIM][TFSI]), 1-butyl-3-methylimidazole tetrafluoroborate ([BMIM][BF4]), 1-ethyl-3-methylimidazole hexafluorophosphate ([EMIM][PF6]) and 1-butyl-3-methylimidazole hexafluorophosphate ([BMIM][PF6]); the anionic group thereof can spontaneously exchange with the halogen atom of the coupling agent in an organic solvent.
[0056] In the modified solid electrolyte powder provided by the embodiment of the present invention, the coating layer is uniform and dense, and its thickness can be within 10nm, such as 4-6nm. The modified solid electrolyte powder has a certain hydrophobicity, and the water contact angle can be 100°-110°; its initial residual alkali content is less than 0.2wt%.
[0057] The embodiment of the present invention uses low-cost silane coupling agents and hydrophobic ionic liquids to form a coating layer on the surface of powders such as LLZO, which has the dual functions of hydrophobicity and ion conductivity; the coating layer has a strong ability to bind to the powder, and can prevent contamination by residual alkali LiOH and LiCO3 when placed in the air, making it easy to store. In the application of positive electrode ternary material blending, it can reduce the harm of residual alkali to the positive electrode material, facilitate positive electrode homogenization, and while achieving the hydrophobic effect, it can also reduce the interface impedance between LLZO and the positive electrode material, improve the ionic conductivity of the positive electrode material, and improve the cycle stability and safety of the battery cell.
[0058] In the embodiment of the present invention, the modification of powders such as LLZO can be completed directly during the powder sand milling process. The high-energy surface generated when the powder particle size is reduced provides a large number of active sites for the coupling agent modification, thereby improving the modification efficiency. Only a simple subsequent stirring treatment is required, and no additional equipment and complex processes are required, which is easy to produce in large quantities and at low cost. In the embodiment of the present invention, the surface modification of powders such as LLZO does not require the use of high temperature environments, thereby avoiding the generation of other harmful byproducts attached to the surface of the LLZO powder due to high temperature reactions, thereby saving resources.
[0059] The present invention provides a positive electrode sheet, comprising a positive electrode active material, and further comprising: the modified solid electrolyte powder as described above or the modified solid electrolyte powder obtained by the preparation method as described above.
[0060] The present invention also provides a lithium-ion battery, which includes the positive electrode sheet. Among them, the embodiment of the present invention also provides a lithium-ion battery containing the modified LLZO powder.
[0061] In an embodiment of the present invention, the positive electrode active material is one or more of lithium cobalt oxide, lithium iron phosphate and a ternary positive electrode material, mainly in the ternary positive electrode material LiNi x Co y Mn z Specifically, the mass ratio of the positive electrode active material to the modified solid electrolyte powder is (97-98): (0.1-1).
[0062] The present invention has no special restrictions on other components of the positive electrode sheet and other parts of the lithium-ion battery. For example, the positive electrode sheet includes a commonly used conductive agent and a binder, and the negative electrode uses a metal lithium sheet.
[0063] In the embodiment of the present invention, the positive electrode slurry including positive electrode active materials, modified solid electrolyte powders, etc. can be controlled to have a theoretical solid content of 65% to 75%; after scraping and baking, a positive electrode sheet can be obtained. In addition, the electrolyte can be a 1 mol / L lithium hexafluorophosphate (LiPF6) solution (other commonly used lithium salts can also be used), and the solvent is preferably a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). In the embodiment of the present invention, the positive electrode sheet, diaphragm, negative electrode, etc. are conventionally assembled to obtain a lithium-ion battery. Based on the effect of positive electrode mixing, the lithium-ion battery has good electrochemical properties.
[0064] In order to better illustrate the present invention, the following examples are further illustrated. Unless otherwise specified, the various reagents and raw materials used in the present invention are all commercially available products or products that can be prepared by recognized methods. Unless otherwise specified, the ratios involved are all mass ratios.
[0065] Example 1
[0066] Ethanol and deionized water were fully mixed in a beaker at a mass ratio of 8:1, and stirred on a magnetic stirrer at a speed of 1000 r / min for 10 minutes to form a solution A. Heptafluorodecyltrimethoxysilane (i.e., perfluorodecyltrimethoxysilane) was slowly added dropwise to solution A, and the mass ratio of heptafluorodecyltrimethoxysilane to solution A was 1:40. Then, glacial acetic acid was added dropwise to solution A to adjust the pH value to 3.2, and stirred at a speed of 1500 r / min and 60°C for 2 hours to fully hydrolyze the silane coupling agent to obtain a solution B.
[0067] LLZO powder was dispersed in anhydrous ethanol, and a high-speed stirrer was used to stir and disperse for 1 h at a speed of 1500 r / min to form slurry C, in which the mass ratio of LLZO powder to ethanol was 3:7; then a sand mill was used to refine the particle size (the diameter of the sand milled zirconium ball was 0.3 mm, and the sand mill speed was 2000 r / min), and the particle size of 562 nm was taken as the standard, and the time was about 3 to 4 h. Solution B was added before the start of sand milling, and the mass ratio of solution B to slurry C was 10:85. The preliminary modified LLZO slurry D was obtained by sand milling. Ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate was added to slurry D to form slurry E, and the mass ratio of 1-butyl-3-methylimidazolium hexafluorophosphate to slurry D was 1:10. Slurry E was dispersed at 80°C with a magnetic stirrer at a speed of 2000 r / min for 3 h. Afterwards, the dispersed slurry E was dried in a 200° C. forced air drying oven to obtain modified LLZO powder after 6 h, which was then ground in an agate mortar to obtain the final modified LLZO powder.
[0068] The present invention performs infrared spectrum test and transmission electron microscope morphology test on the modified LLZO powder; wherein, Figure 2 It can be seen from the infrared spectrum that the wave number is 3430cm -1 The peak near 1634cm is the deformation stretching vibration peak of OH. The peak intensity of the modified powder at this position is significantly reduced, indicating that the dual-functional modification layer has removed a large number of hydroxyl groups on the surface of LLZO powder, proving that the modification is successful. -1 The peaks nearby are caused by the bending vibration of H2O. The obvious decrease in the peak intensity at this position indicates that the adsorbed water content on the surface of the modified powder is extremely small, proving its hydrophobicity.
[0069] Figure 3 This is a transmission electron microscope image of the modified LLZO powder. The image in the upper right corner corresponds to the LLZO powder lattice fringes. According to the middle part of the yellow dotted line in the figure, it can be clearly seen that the powder surface has a uniform and dense coating layer with a thickness of about 5nm.
[0070] In addition, the contact angle of LLZO powder to water was tested before and after modification. Figure 4 The figure is the contact angle of the powder to water when dry-pressed before and after modification. Before modification, the wettability to water is very large and the contact angle is also very small (13.4°). After modification, the contact angle of the powder to water increases significantly to 109.9°. It is not wettable to water, indicating that the hydrophobic effect has been achieved.
[0071] Example 2
[0072] Ethanol and deionized water were fully mixed in a beaker at a mass ratio of 8:1, and stirred on a magnetic stirrer at a speed of 1000 r / min for 10 minutes to form solution A. Nonafluorohexyltrimethoxysilane was slowly added dropwise to solution A. The mass ratio of nonafluorohexyltrimethoxysilane to solution A was 1:40. Then, glacial acetic acid was added dropwise to solution A to adjust the pH value to 3.2. The solution was stirred at a speed of 1500 r / min and 60°C for 2 hours to fully hydrolyze the silane coupling agent to obtain solution B.
[0073] LLZO powder was dispersed in anhydrous ethanol, and a high-speed stirrer was used to stir and disperse for 1 h at a speed of 1500 r / min to form slurry C, wherein the mass ratio of LLZO powder to ethanol was 3:7, and then a sand mill was used to refine the particle size, with the particle size of 562 nm being the standard, and the time was about 3 to 4 h. Solution B was added before the start of sand milling, and the mass ratio of solution B to slurry C was 10:85. The preliminary modified LLZO slurry D was obtained by sand milling. Ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate was added to slurry D to form slurry E, and the mass ratio of 1-butyl-3-methylimidazolium hexafluorophosphate to slurry D was 1:10. Slurry E was dispersed at 80°C with a magnetic stirrer at a speed of 2000 r / min for 3 h. Afterwards, the dispersed slurry E was dried in a 200° C. forced air drying oven to obtain modified LLZO powder after 6 h, which was then ground in an agate mortar to obtain the final modified LLZO powder.
[0074] Example 3
[0075] Ethanol and deionized water were fully mixed in a mass ratio of 8:1 in a beaker, and stirred on a magnetic stirrer at a speed of 1000 r / min for 10 minutes to form a solution A. Heptafluorodecyltrimethoxysilane was slowly added dropwise to solution A. The mass ratio of heptafluorodecyltrimethoxysilane to solution A was 1:40. Then, glacial acetic acid was added dropwise to solution A to adjust the pH value to 3.2. The solution was stirred at a speed of 1500 r / min and 60°C for 2 hours to fully hydrolyze the silane coupling agent to obtain a solution B.
[0076] LLZO powder was dispersed in anhydrous ethanol, and a high-speed stirrer was used to stir and disperse at a speed of 1500r / min for 1h to form slurry C, wherein the mass ratio of LLZO powder to ethanol was 3:7, and then a sand mill was used to refine the particle size, with the particle size of 562nm being the standard, and the time was about 3 to 4h. Solution B was added before the start of sand milling, and the mass ratio of solution B to slurry C was 20:85. The preliminary modified LLZO slurry D was obtained by sand milling. Ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate was added to slurry D to form slurry E, and the mass ratio of 1-butyl-3-methylimidazolium hexafluorophosphate to slurry D was 1:10. Slurry E was dispersed at 80°C with a magnetic stirrer at a speed of 2000r / min for 3h. Afterwards, the dispersed slurry E was dried in a 200° C. forced air drying oven to obtain modified LLZO powder after 6 h, which was then ground in an agate mortar to obtain the final modified LLZO powder.
[0077] Example 4
[0078] Ethanol and deionized water were fully mixed in a mass ratio of 8:1 in a beaker, and stirred on a magnetic stirrer at a speed of 1000 r / min for 10 minutes to form a solution A. Heptafluorodecyltrimethoxysilane was slowly added dropwise to solution A. The mass ratio of heptafluorodecyltrimethoxysilane to solution A was 1:40. Then, glacial acetic acid was added dropwise to solution A to adjust the pH value to 3.2. The solution was stirred at a speed of 1500 r / min and 60°C for 2 hours to fully hydrolyze the silane coupling agent to obtain a solution B.
[0079] LLZO powder was dispersed in anhydrous ethanol, and a high-speed stirrer was used to stir and disperse for 1 h at a speed of 1500 r / min to form slurry C, wherein the mass ratio of LLZO powder to ethanol was 3:7, and then a sand mill was used to refine the particle size, with the particle size of 562 nm being the standard, and the time was about 3 to 4 h. Solution B was added before the start of sand milling, and the mass ratio of solution B to slurry C was 20:85. The preliminary modified LLZO slurry D was obtained by sand milling. Ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate was added to slurry D to form slurry E, and the mass ratio of 1-butyl-3-methylimidazolium hexafluorophosphate to slurry D was 1:5. Slurry E was dispersed at 80°C with a magnetic stirrer at a speed of 2000 r / min for 3 h. Afterwards, the dispersed slurry E was dried in a 200° C. forced air drying oven to obtain modified LLZO powder after 6 h, which was then ground in an agate mortar to obtain the final modified LLZO powder.
[0080] Comparative Example 1
[0081] The LLZO powder was dispersed in ethanol and stirred and dispersed for 1 h using a high-speed stirrer at a speed of 1500 r / min to form slurry A, in which the mass ratio of LLZO powder to ethanol was 3:7. Then, a sand mill was used to refine the particle size, and the sand milled slurry was recorded as slurry B. Slurry B was dried in a 200°C forced air drying oven to obtain unmodified LLZO powder after 6 h, which was then ground in an agate mortar to obtain the final LLZO powder.
[0082] Comparative Example 2
[0083] Al2O3 powder was dispersed in ethanol and stirred and dispersed at a speed of 1500r / min for 1h in a high-speed stirrer to form slurry A, in which the mass ratio of Al2O3 powder to ethanol was 3:7. Then a sand mill was used to refine the particle size, which was recorded as slurry B after sand grinding. Slurry B was dried in a 200°C forced air drying oven for 6h to obtain unmodified Al2O3 powder, which was then ground in an agate mortar to obtain the final Al2O3 powder.
[0084] Comparative Example 3
[0085] Al2O3 powder was used to replace the LLZO powder in Example 1, and the other steps were the same to obtain modified Al2O3 powder.
[0086] Comparative Example 4
[0087] Comparative Example 4 is that LLZO powder is not mixed in the positive electrode homogenization process, and the ternary positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 The mass ratio of O2 (hereinafter referred to as NCM811), conductive carbon black SP, and PVDF is 97.8:1.2:1; other preparation conditions of button cells and testing are the same as those in Example 1.
[0088] The LLZO and Al2O3 powders obtained in Examples 1-4 and Comparative Examples 1-4 were subjected to surface residual alkali and moisture determination, and assembled into button cells for electrochemical performance testing. The specific contents are as follows:
[0089] 1. Determination of residual alkali on the surface of LLZO powder
[0090] Disperse 10g LLZO in 100g deionized water, use a high-speed stirrer to disperse for 30 minutes, filter through filter paper to obtain a clear solution containing LiOH and LiCO3, titrate with the prepared 0.1M dilute hydrochloric acid, use methyl orange as the calibration indicator, observe the change of the indicator and the amount of dilute hydrochloric acid consumed, and calculate the content of residual alkali LiOH and LiCO3.
[0091] 2. Assembly and testing of button cells in the present invention
[0092] The ternary positive electrode material NCM811, conductive carbon black SP, PVDF, and LLZO / Al2O3 powders were mixed in a high-speed mixer in a mass ratio of 97.3:1.2:1:0.5, and N-methylpyrrolidone (NMP) was added as a solvent. The theoretical solid content was controlled to be 72%, the rotation speed was 2000r / min, and the mixture was stirred for 2h. The mixed slurry was evenly coated on a 17μm aluminum foil with a scraper, and was cut into positive electrode discs with a diameter of 12mm with a punch. The positive electrode was baked, and a metal lithium sheet was used as the negative electrode. The electrolyte was a 1mol / L LiPF6 EC / EMC / DMC solution. The positive electrode sheet, polyethylene diaphragm, lithium sheet, shrapnel, gasket, positive and negative electrode shells were assembled into button batteries in a glove box filled with argon in sequence and fully soaked for 12h. The entire slurrying, coating, cutting and assembly were carried out in a dry room with a dew point of -40℃.
[0093] The prepared lithium-ion battery was placed in a constant temperature environment of 25°C for 3 hours to keep the temperature inside and outside the battery stable. It was charged to 4.2V at a constant current and voltage of 0.1C (1C = 192mAh / g), and discharged to 3V at a constant current of 0.1C to test the first cycle charge and discharge capacity and coulomb efficiency. Coulomb efficiency = first cycle discharge specific capacity / first cycle charge specific capacity*100%.
[0094] The prepared lithium-ion battery was placed in a constant temperature environment of 25°C for 3 h, keeping the temperature inside and outside the battery stable, and charged to 4.2 V at a constant current and constant voltage of 1C (1C=192 mAh / g), and discharged to 3 V at a constant current of 1C for 500 cycles, and the capacity retention rate was calculated. The capacity retention rate of the nth cycle (%) = (discharge specific capacity of the nth cycle / discharge specific capacity of the first cycle) * 100%.
[0095] The moisture content, residual alkali content and pH value of Examples 1-4 and Comparative Example 1 were tested. After being placed under constant temperature and humidity conditions for 3 days, 7 days and 15 days, the growth rates of moisture content and residual alkali were tested. The test data are shown in Table 1.
[0096] Table 1 Comparative test results of residual alkali content in the embodiments of the present invention
[0097]
[0098] It can be seen from Examples 1-4 and Comparative Example 1 in Table 1 that the LLZO solid electrolyte powder treated with a dual-functional layer coating of a silane coupling agent and an ionic liquid exhibits a lower residual alkali content than the untreated LLZO powder, the pH of the modified LLZO powder is slightly reduced, and the absorption of moisture after storage is reduced, indicating that the method of the present invention can effectively improve the sensitivity of LLZO to air and water.
[0099] The powders prepared in Examples 1-4 and Comparative Examples 1-4 were mixed into the positive electrode material NCM811. At 25°C, the powders were charged to 4.2V at 0.1C constant current and constant voltage, and discharged to 3V at 0.1C constant current to test the first cycle charge and discharge capacity and coulomb efficiency. The powders were charged to 4.2V at 1C constant current and constant voltage, and discharged to 3V at 1C constant current to test the capacity retention rate (1C=192mAh / g). The results are shown in Table 2.
[0100] Table 2 Comparative test results of battery performance of the present invention embodiment
[0101]
[0102] Comparing Examples 1, 2, 3, and 4 with Comparative Examples 2, 3, and 4, it is shown that LLZO blending improves the gram capacity and coulomb efficiency of NCM811 materials. This is because LLZO, as an ion conductor, provides an effective ion transmission path, promotes the use of capacity, replenishes lithium for active materials during the cycle, improves the stability of the positive electrode material, homogenizes the lithium ion flux, and improves the cycle performance. The presence of residual alkali will accelerate the attenuation of the capacity of the NCM811 positive electrode material. Comparing Examples 1, 2, 3, and 4 with Comparative Example 1, it is shown that the LLZO surface modified by the double-functional layer coating has a low residual alkali content, effectively reduces the interface impedance, and inhibits the occurrence of residual alkali reactions with other components. The capacity retention rate is high after 500 cycles of 1C / 1C.
[0103] It can be seen from the above embodiments that the embodiments of the present invention mix the hydrophobically modified LLZO and other powders into the NCM811 positive electrode material, and modify the hydrophobic and ion-conductive dual-functional coating layer on the surface of the oxide electrolyte powder to provide a continuous ion transmission path, improve the capacity and cycle performance of the positive electrode material, homogenize the lithium ion flux, remove the LLZO surface byproducts, and reduce the interface impedance between LLZO and the positive electrode material. In addition, this blending method can be applied to other positive electrode material systems, such as lithium iron phosphate and lithium cobalt oxide. The entire process of the present invention does not require additional equipment and complex processes, and can be operated on the basis of existing equipment. No toxic or harmful substances are produced during the coating process, and it is easy to produce in large quantities.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A modified solid electrolyte powder, characterized in that: The invention comprises an oxide solid electrolyte substrate and a coating layer formed on the surface of the substrate, wherein the coating layer is formed by assembling a silane coupling agent and a hydrophobic ionic liquid.
2. The modified solid electrolyte powder according to claim 1, characterized in that: The oxide solid electrolyte substrate is composed of LISICON type, garnet type, perovskite type or NASICON type oxide electrolyte.
3. The modified solid electrolyte powder according to claim 1, characterized in that: The thickness of the coating layer is within 10 nm; the initial residual alkali content of the modified solid electrolyte powder is lower than 0.2 wt%.
4. A method for preparing a modified solid electrolyte powder, characterized in that: The following steps are involved: Providing a hydrolyzate of a silane coupling agent; The oxide solid electrolyte powder and the hydrolyzate of the silane coupling agent are mixed and reacted to obtain an intermediate powder; The hydrophobic ionic liquid is mixed with the intermediate powder and reacted to obtain a modified solid electrolyte powder with a coating layer on the surface.
5. The preparation method according to claim 4, characterized in that: The silane coupling agent is a fluorinated alkyl trialkoxysilane and / or a trimethoxyalkyl silane, and further is one or more of nonafluorohexyltrimethoxysilane, heptadecafluorooctyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, trimethoxyoctadecylsilane, trimethoxyhexadecylsilane, trimethoxydodecylsilane, trimethoxy-n-propylsilane and trimethoxymethylsilane.
6. The preparation method according to claim 5, characterized in that: The preparation of the hydrolyzate of the silane coupling agent comprises: hydrolyzing the silane coupling agent in a mixed solution of ethanol and water, wherein the mass ratio of ethanol to water in the mixed solution is (5-10):1, the temperature of the hydrolysis reaction is 50-90°C, the time is 1-2h, and the pH value is adjusted to 2-4 to obtain a hydrolyzed solution of the silane coupling agent.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The oxide solid electrolyte powder is LLZO powder, and is mixed with the hydrolyzate of the silane coupling agent in the form of an ethanol dispersion, and the mass ratio of the oxide solid electrolyte powder to ethanol is (10-30): (70-90); an intermediate powder ethanol dispersion is obtained through sand milling.
8. The preparation method according to any one of claims 4 to 6, characterized in that: The hydrophobic ionic liquid is a methylimidazole fluorine-containing ionic liquid, further comprising one or more of 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazole tetrafluoroborate, 1-ethyl-3-methylimidazole hexafluorophosphate and 1-butyl-3-methylimidazole hexafluorophosphate.
9. The preparation method according to claim 8, characterized in that: After the hydrophobic ionic liquid and the intermediate powder are mixed, the mixture is stirred for reaction for 0.5-5 hours and then dried to obtain a modified solid electrolyte powder having a coating layer on the surface.
10. A positive electrode sheet, comprising a positive electrode active material, characterized in that: Also includes: The modified solid electrolyte powder according to any one of claims 1 to 3 or the modified solid electrolyte powder obtained by the preparation method according to any one of claims 4 to 9; The positive electrode active material is one or more of lithium cobalt oxide, lithium iron phosphate and ternary positive electrode materials; the mass ratio of the positive electrode active material to the modified solid electrolyte powder is (97-98): (0.1-1).
11. A lithium ion battery, characterized in that: Including the positive electrode sheet as claimed in claim 10.
Citation Information
Cited By
Surface-activated solid electrolyte particles
WO2026180476A1